Gendering insiders and outsiders. Labour market status and preferences for job security - RECWOWE; Emmenegger, Patrick (Edinburgh, 2010)
"This paper examines the role of gender in the relationship between labour market status and preferences for job security. We hypothesize that the insider/outsider theory of employment and unemployment suffers from a gender bias. It neither takes the possibility of family-related labour market transitions nor the role of the household situation (division of labour, presence of children, dual-earner households etc.) into account. We adapt the insider/outsider theory of employment and unemployment by incorporating the, on average, higher number of labour market transitions experienced by women into the model using interaction effects and by conceptualising the household situation as mobility and responsibility effects. Contrary to our expectations, we find no significant effect of gender on preferences for job security, neither in interaction with labour market status nor as an independent effect. In contrast, we observe that individuals living together with their partners and main contributors to the household income consider job security to be particularly important."